Larval diet affects adult reproduction, but not survival, independent of the effect of injury and infection in Drosophila melanogaster. (October 2022) - Savola, Eevi; Vale, Pedro F.; Walling, Craig A.
Graphical abstract: Highlights: Early-life diet has been shown to affect both juvenile and adult life history traits. Less well known are early-life diet effects on adult responses to infection. We altered larval dietary macronutrient ratio in Drosophila melanogaster . We then infected adult females with a bacterial pathogen Pseudomonas entomophila. Larval diet affected adult reproduction, but not survival, even under infection. Abstract: Early-life conditions have profound effects on many life-history traits, where early-life diet affects both juvenile development, and adult survival and reproduction. Early-life diet also has consequences for the ability of adults to withstand environmental challenges such as starvation, temperature and desiccation. However, it is less well known how early-life diet influences the consequences of infection in adults. Here we test whether varying the larval diet of female Drosophila melanogaster (through altering protein to carbohydrate ratio, P:C) influences the long-term consequences of injury and infection with the bacterial pathogen Pseudomonas entomophila . Given previous work manipulating adult dietary P:C, we predicted that adults from larvae raised on higher P:C diets would have increased reproduction, but shorter lifespans and an increased rate of ageing, and that the lowest larval P:C diets would be particularly detrimental for adult survival in infected individuals. For larval development, we predicted that low P:C would lead to a longer development time and lower viability. We found that early-life and lifetime egg production were highest at intermediate to high larval P:C diets, but this was independent of injury and infection. There was no effect of larval P:C on adult survival. Larval development was quickest on intermediate P:C and egg-to-pupae and egg-to-adult viability were slightly higher on higher P:C. Overall, despite larval P:C affecting several measured traits, we saw no evidence that larval P:C altered the consequence of infection or injury for adult survival or early-life and lifetime reproduction. Taken together, these data suggest that larval diets appear to have a limited impact on the adult life history consequences of infection.